2014
DOI: 10.3130/aija.79.2231
|View full text |Cite
|
Sign up to set email alerts
|

Development From Citizen Participation to Collaboration Relationship on the Process of Public Facility Construction

Abstract: This study focused on citizen participation and collaboration in the process of construction of public facilities. We tried to clarify the definition of citizen participation and collaboration. To be specific, we analyzed how collaborative efforts occurred from citizen participation as they transpired within the confines of an area where the collaborative relationship is being covered. We arranged this publicly-led participative concept of collaboration as it developed and as it eventually led into such a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…According to previous studies, it is desirable for the government, citizens, and experts to have an appropriate organizational structure in place regarding the design of public facilities and the citizens to participate in decision-making processes. 7,8,12 However, during the data compilation in this study, it became apparent that it was difficult to set up such a structure in the midst of emergency disaster recovery efforts. It was found that each municipality chose maintenance methods and policies while seeking out the opinions of its citizens through questionnaires and other means.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to previous studies, it is desirable for the government, citizens, and experts to have an appropriate organizational structure in place regarding the design of public facilities and the citizens to participate in decision-making processes. 7,8,12 However, during the data compilation in this study, it became apparent that it was difficult to set up such a structure in the midst of emergency disaster recovery efforts. It was found that each municipality chose maintenance methods and policies while seeking out the opinions of its citizens through questionnaires and other means.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that, in the case of existing public facilities, citizen participation in the maintenance process develops into citizen-municipality collaboration, and building a framework for citizen participation, beginning with the planning stage, leads to sustainable citizen participation management. 7,8 In addition, Miyagi Prefecture has stated that it is necessary to use the earthquake ruins to teach earthquake-related lessons based on the opinions gathered at a conference of experts, and that the government, organizations, and citizens of the prefecture must participate in imparting them to others. 9 In the Tohoku region, where a declining birthrate and an aging population are anticipated in the future, sustainable preservation and the use of earthquake ruins are issues that should be addressed.…”
Section: Background/research Purposementioning
confidence: 99%
See 3 more Smart Citations